Dimensional Perspectives of Human Resource Development - Chaudhary , Kanun Lal (Prajnik Bimarsha प्राज्ञिक विमर्श, 2024)
Human Resource Management (HRM) is a collective term for all the formal systems created to help in managing employees and other stakeholders within an organization. It is tasked with four main functions, namely, the recruitment, utilization, development and motivation of employees. Ideally, the role of HRM is to find the best way to increase the productivity of an organization through its employees. Until recently, an organisation’s human resource department was categorized in the lower rungs. This is surprising considering the crucial role that this department plays in replenishing and nourishing an organization’s resources. It has transformed significantly from the task-oriented nature of administration it used to be in the 1980s. It is now viewed as a strategy-focused extension of every organisation. This department thrives on specific principles, such as commitment and competence, Another core function of HRM is employee orientation and development. Orientation is the process of teaching new recruits the necessary skills, knowledge, and behaviors so that they can transition to the new organisation effectively. Employee orientation is a broad process conducted by the HR department, and it’s done through different methods, including lectures, meetings, videos, mentoring, and team-building exercises. The main objective of the orientation is to provide new recruits with adequate information regarding the organisation’s targets, rules, policies, and activities. Employee development refers to all the efforts for improving individual, team, and organizational effectiveness. One aspect the human resource department tackles is talent development. This involves aligning the employees’ skills with the organisation’s needs. In addition to hiring, training, and orienting employees, HRM should also improve their career opportunities.